2008
DOI: 10.1111/j.1463-1326.2008.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of sitagliptin in patients with type 2 diabetes and chronic renal insufficiency

Abstract: In this study, sitagliptin was generally well tolerated and provided effective glycaemic control in patients with type 2 diabetes and moderate to severe renal insufficiency, including patients with ESRD on dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
191
0
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(206 citation statements)
references
References 25 publications
5
191
0
10
Order By: Relevance
“…With dose adjustment in a 54-week trial, sitagliptin was generally well tolerated and provided effective glycaemic control in patients with T2DM and moderate-to-severe RI, including patients with ESRD on dialysis [83]. However, in a study assessing dose adjustments of glucose-lowering agents in T2DM patients with moderate to end-stage RI from a large outpatients electronic medical records database, only 15% of patients with prescriptions for sitagliptin received dosages of the drug appropriate for their degree of RI.…”
Section: Patients With Renal Impairmentmentioning
confidence: 99%
“…With dose adjustment in a 54-week trial, sitagliptin was generally well tolerated and provided effective glycaemic control in patients with T2DM and moderate-to-severe RI, including patients with ESRD on dialysis [83]. However, in a study assessing dose adjustments of glucose-lowering agents in T2DM patients with moderate to end-stage RI from a large outpatients electronic medical records database, only 15% of patients with prescriptions for sitagliptin received dosages of the drug appropriate for their degree of RI.…”
Section: Patients With Renal Impairmentmentioning
confidence: 99%
“…However, Park et al [9] reported that sitagliptin showed a much higher efficacy compared to that of vildagliptin and linagliptin. In Table 2 Vital and serum parameters determined before and during the study treating T2DM patients with stages 3 to 5 chronic kidney disease (CKD) including those with end-stage renal disease, sitagliptin has been reported to be effective in controlling plasma glucose levels and maintaining the safety [11][12][13]. However, these reports only discussed the plasma glucose control mainly by measuring HbA1c, and the targets of DPP-4 inhibitors to achieve good glycemic control, such as aGLP-1, have not been discussed.…”
Section: Discussionmentioning
confidence: 99%
“…The sub-analysis of the Trial Evaluating Cardiovascular Outcomes with Sitagliptin study (TECOS) to evaluate cardiovascular outcome in mainly normoalbuminuric T2DM patients receiving sitagliptin showed that mean change of eGFR during 48 months from the baseline was significantly lower in the sitagliptin group than in the placebo group, but the cumulative incidence of microalbuminuria and renal failure was equivalent in two groups [15]. The efficacy and safety of sitagliptin had also been reported in patients with renal failure [11][12][13]. Taking these reports together into consideration, subtle changes in renal function caused by sitagliptin might be generally safe.…”
Section: Discussionmentioning
confidence: 99%
“…7 Recent data suggest that sitagliptin is well tolerated and provides effective glycemic control in patients with type 2 diabetes with moderate to severe renal insufficiency, including patients on dialysis. 13 To our knowledge, no data exist examining the potentially inappropriate dosing of sitagliptin based on manufacturer guidelines.…”
Section: ■■ Resultsmentioning
confidence: 99%